2022
DOI: 10.3233/jad-220082
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Orexin-A Levels in Prodromal Dementia with Lewy Bodies

Abstract: Background: Studies on plasma orexin-A levels in prodromal dementia with Lewy bodies (DLB) and the relationship with clinical manifestations are rare. Objective: To assess plasma orexin-A levels and evaluate the correlation with clinical features in patients with mild cognitive impairment with Lewy bodies (MCI-LB) and DLB. Methods: Plasma orexin-A levels were measured in 41 patients with MCI-LB, 53 with DLB, and 48 healthy controls (HCs). Informant-based history, neurological examinations, neuropsychological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Neuropsychiatric symptoms: rates of neuropsychiatric supportive symptoms in the MCI-LB criteria (hallucinations in non-visual modalities, systematized delusions, apathy, anxiety, and depression) were reported in up to seven studies. 23 29 When comparing MCI-LB with MCI-AD, our meta-analyses showed that the pooled prevalence of anxiety (31% vs. 18%), depression (37% vs. 22%), apathy (47% vs. 23%) and delusions (11% vs. 4%) was higher in MCI-LB ( Table 2 ). We found no difference for non-visual hallucinations (7% vs. 3%), though this feature was only recorded in three studies ( Table 2 ).…”
Section: Resultsmentioning
confidence: 95%
“…Neuropsychiatric symptoms: rates of neuropsychiatric supportive symptoms in the MCI-LB criteria (hallucinations in non-visual modalities, systematized delusions, apathy, anxiety, and depression) were reported in up to seven studies. 23 29 When comparing MCI-LB with MCI-AD, our meta-analyses showed that the pooled prevalence of anxiety (31% vs. 18%), depression (37% vs. 22%), apathy (47% vs. 23%) and delusions (11% vs. 4%) was higher in MCI-LB ( Table 2 ). We found no difference for non-visual hallucinations (7% vs. 3%), though this feature was only recorded in three studies ( Table 2 ).…”
Section: Resultsmentioning
confidence: 95%
“…CSF cut-off values for Aβ-positive or Aβ-negative were Aβ1-42 < 550 pg/mL and/or Aβ1-42/Aβ1-40 ratio ≤ 0.05. CSF cut-off values for tau positive were p-tau181 > 50 pg/mL and/or t-tau > 399 pg/mL, all cut-off values were set based on the accumulation of previous experimental data of Kindstar Global Genetic Technology Co., LTD. APOE genotype was determined based on genomic DNA using polymerase chain reaction following the detailed protocol described in our previous study (Gan et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Multiplanar oblique coronal (perpendicular to the axis of the hippocampus), transverse, and coronal position reconstructions were made of 3D T1-weighted images for diagnostic multisequence MRI; details of the protocol are provided in our previous study (Zhu et al, 2021 ; Gan et al, 2022 ). All MRI visual scales readings were reviewed by two experienced neuroradiologists in a double-blind manner and the final rating scores averaged.…”
Section: Methodsmentioning
confidence: 99%
“…We used peripheral blood to extract genomic DNA, and polymerase chain reaction was amplified to determine the APOE gene in this study. All the detailed method had been described at our previous study [ 27 ]. We were sure about all genotypes without knowledge of the patient status.…”
Section: Methodsmentioning
confidence: 99%